2021
DOI: 10.1002/jlb.3a1220-789rr
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 regulates neutrophil extracellular trap formation and lung injury in abdominal sepsis

Abstract: Neutrophil extracellular traps (NETs)‐mediated tissue damage is a hallmark in abdominal sepsis. Under certain conditions, microRNAs (miRs) can regulate protein expression and cellular functions. The aim of this study was to investigate the role of miR‐155 in sepsis‐induced NET formation, lung inflammation, and tissue damage. Abdominal sepsis was induced in wild‐type (WT) C57BL/6 and miR‐155 gene‐deficient mice by cecal ligation and puncture (CLP). The amount of DNA–histone complex formation as well as myeloper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…24 , 39 , 40 Furthermore, preclinical studies have shown a great potential for anti-NET strategies in limiting inflammation-associated collateral damage in sepsis models. 23 , 38 , 41 43 Our study confirms these earlier reports, in that we found that NET inhibition or NET degradation significantly improved outcomes in a mouse model of neonatal peritonitis. Targeting NETs reduced the levels of inflammatory cytokines in the peritoneal cavity and reduced circulating platelet–neutrophil aggregates, a sensitive marker for systemic platelet activation.…”
Section: Discussionsupporting
confidence: 90%
“…24 , 39 , 40 Furthermore, preclinical studies have shown a great potential for anti-NET strategies in limiting inflammation-associated collateral damage in sepsis models. 23 , 38 , 41 43 Our study confirms these earlier reports, in that we found that NET inhibition or NET degradation significantly improved outcomes in a mouse model of neonatal peritonitis. Targeting NETs reduced the levels of inflammatory cytokines in the peritoneal cavity and reduced circulating platelet–neutrophil aggregates, a sensitive marker for systemic platelet activation.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Wu et al reported that overexpression of miR-155 promoted the chronic intermittent hypoxia-induced NLRP3 inflammasome activation in renal tubular cells [ 34 ]. Additionally, Hawez et al revealed that miR-155 regulates the pulmonary formation of neutrophil extracellular traps in abdominal sepsis [ 35 ]. More importantly, miR-155 has been noted to be highly expressed in COPD, while miR-155 deficiency notably suppressed CSE-mediated lung inflammation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these authors showed that miR-155/ PAD4 interaction after transfection of human neutrophils with miR-155 mimic or inhibitor correlated with NET formation capacity in vitro [50]. Furthermore, miR-155 deficiency in a murine model of abdominal sepsis decreased the intrinsic capacity of neutrophils to generate NETs and attenuated the levels of NETs in the lungs [51 ▪ ].…”
Section: Do Mirnas Regulate Cells Involved In Thrombo-inflammation?mentioning
confidence: 94%